Cytotoxicity evaluation of methacrylate- and silorane-based composite resins - Digdem Eren; Gulsah Goktolga Akin; Ozden Ozel Bektas; Zubeyde Akin Polat (Cumhuriyet University, 2012)
Objectives: The objective of this study was to investigate and compare the cytotoxic effects of four composite resin materials with different content. Material and Methods: Two traditional methacrylate-based (Clearfil AP-X, RefleXions), as well as a self-adhering methacrylate-based (Vertise Flow) and a silorane-based (Filtek Silorane) composite resin were tested in the experiment. Ten cylindrical specimens were made of each material, using a mould (2mm. thick and 8 mm. in diameter). An agar diffusion method was employed, and cytotoxicity rankings were determined using lysis index scores. For statistical analysis, Kruskal-Wallis and Mann-Whitney U-tests were used. Results: Amongst the composite resins, the silorane-based composite was found to be less cytotoxic than the methacrylate-based composite resins, which all had the same cytotoxicity ranking. Conclusions: The silorane-based composite resin was considered more biocompatible than the methacrylate-based composite resins.